Embodiment is Ecological: The Metabolic Lives of Whey Protein Powder. (March 2020) - King, Samantha; Weedon, Gavin
This article explores the metabolic lives of whey powder, the most popular form of protein supplement in what has become a multibillion-dollar industry during the past two decades. Faced with the slippery and elusive properties latent to this multiplicitous substance, our approach is to follow whey powder from its mid-20th century emergence as a noxious byproduct of industrial dairy production, through the human and animal bodies unevenly tasked with its processing, and out into waterways, where its nitrogen density rematerializes as a pollutant. We show how whey powder emerged as a solution to the environmental damage posed by whey pollution, how such damage is an effect of the systematic overproduction endemic to agrofood industries and how whey's toxicity persists through processes of metabolism and consumption, despite attempts to process and profit from its vital capacities. Throughout, we argue that whey exemplifies ecological embodiment, understood as the co-constitutive relations between bodily matter and ecological life, and their entanglement with processes of commodification.